Noncoding RNA Expression and Targeted Next-Generation Sequencing Distinguish Tubulocystic Renal Cell Carcinoma (TC-RCC) from Other Renal Neoplasms - Lawrie, Charles H; Armesto, María; Fernandez-Mercado, Marta; Arestín, María; Manterola, Lorea; Goicoechea, Ibai; Larrea, Erika; Caffarel, María M; Araujo, Angela M; Sole, Carla; Sperga, Maris; Alvarado-Cabrero, Isabel; et al. (The Journal of molecular diagnostics, 2018)
Tubulocystic renal cell carcinoma (TC-RCC) is a rare recently described renal neoplasm characterized by gross, microscopic, and immunohistochemical differences from other renal tumor types and was recently classified as a distinct entity. However, this distinction remains controversial particularly because some genetic studies suggest a close relationship with papillary RCC (PRCC). The molecular basis of this disease remains largely unexplored. We therefore performed noncoding (nc) RNA/miRNA expression analysis and targeted next-generation sequencing mutational profiling on 13 TC-RCC cases (11 pure, two mixed TC-RCC/PRCC) and compared with other renal neoplasms. The expression profile of miRNAs and other ncRNAs in TC-RCC was distinct and validated 10 differentially expressed miRNAs by quantitative RT-PCR, including miR-155 and miR-34a, that were significantly down-regulated compared with PRCC cases (n = 22). With the use of targeted next-generation sequencing we identified mutations in 14 different genes, most frequently (>60% of TC-RCC cases) in ABL1 and PDFGRA genes. These mutations were present in <5% of clear cell RCC, PRCC, or chromophobe RCC cases (n > 600) of The Cancer Genome Atlas database. In summary, this study is by far the largest molecular study of TC-RCC cases and the first to investigate either ncRNA expression or their genomic profile. These results add molecular evidence that TC-RCC is indeed a distinct entity from PRCC and other renal neoplasms.
Keywords: nekódující RNA; mikro RNA; vysoce účinné nukleotidové sekvenování; regulace genové exprese u nádorů; Carcinoma, Renal Cell; Gene Expression Profiling; lidé; Diagnosis, Differential; MicroRNAs; reprodukovatelnost výsledků; mutace; diferenciální diagnóza; karcinom z renálních buněk; stanovení celkové genové exprese; Reproducibility of Results; Kidney Neoplasms; RNA, Untranslated; Mutation; Humans; Gene Expression Regulation, Neoplastic; High-Throughput Nucleotide Sequencing; nádory ledvin